Intelligenz im Zeitalter ihrer technischen Reproduzierbarkeit: Zur Dialektik artifizieller Vernunft - Schubert, Alexander (Revista Eletrônica Estudos Hegelianos, 2025)
The steady rise of generative AI raises the question of what impact the technical reproducibility of intelligence has on our thinking in general and our understanding of reason in particular. There are different opinions on the question whether AI can develop something like a humanoid consciousness and whether it represents an opportunity or a threat for the future. In this essay, I discuss this question with reference to the dialectic of (self-)consciousness as laid out by Hegel in his philosophy of spirit. I will examine the thesis that artificial intelligence represents the consequent further development of what Hegel called “verständiges Denken”. Building on Max Horkheimer’s "critique of instrumental reason”, I will outline the commonalities and differences between natural and artificial intelligence, showing that the dialectical ambiguity of the former is continued in the latter and that emancipatory and totalitarian tendencies go hand in hand in both. That is why the task of philosophy is not to play the two off against each other, but to work out the emancipatory potential in both and to protect both of them against the danger of totalitarian thinking.